Optimization of mobile driving licenses in improving public services by the Garut Police Traffic Unit Regident - Putra, Muh. Evan Rafli Batara (Police Studies Review, 2023)
This research was motivated by the high number of enforcement of traffic violations for drivers without a SIM committed by the Garut Police Traffic Unit. One form of innovation to improve public services has been carried out by the Garut Polres Satlantas Regident Unit through the implementation of a Mobile SIM to make it easier for remote communities who are constrained by distance problems to extend their SIM. However, in practice it is not in accordance with the main purpose of the innovation made. Therefore, a study was carried out which aimed to describe the implementation of a mobile driver’s license in improving public services by the Garut Police Traffic Unit Regident Unit, the Unit regident’s efforts to optimize these innovations, and the influencing factors. This research was conducted using a qualitative approach that focused on optimizing mobile driving licenses located in Garut Regency, data collection techniques by interview, observation, and document review, data validity by using data triangulation with primary and secondary data sources as well as data analysis techniques in the form of data reduction, presentation data, and drawing conclusions. The results of the study found that the optimization of driving licenses in improving public services by the Garut Police Traffic Unit Residents analyzed by management theory and Article 21 of Law Number 25 of 2009 is appropriate to be implemented at the Garut Police. The implementation of mobile driving licenses is quite good with the fulfillment of the indicators contained in article 21 of Law Number 25 of 2009. However, there are still obstacles in terms of waiting room facilities, costing, and guaranteed service certainty, especially in determining schedules to reach areas remote areas of Garut Regency. Analysis of the Regident Unit’s efforts to optimize mobile driving licenses has been going well, but needs to be improved in the supervisory and organizational functions. Meanwhile, the most influential factors are market factors related to the applicant’s license extension (public interest) and road infrastructure. Based on the results of the study, the researchers suggest comprehensive socialization to the public through various media and cooperation with cellular operators, proposals for education and training for SIM examiner certification for mobile SIM officers, increasing supervision and coordination within the Garut Police Traffic Unit Regident in order to achieve public satisfaction.